Patient-Reported Outcomes After a Modified Albee Procedure. Issue 11 (18th November 2021) - Bevan, Patrick J.; Farrow, Lutul D.; Warren, Jared; Hooper, Perry O.; Kroneberger, Elisabeth; Andrish, Jack T.
Background: Trochlear dysplasia (TD) is a recognized condition that can become a risk factor for patellofemoral instability. A modified Albee osteotomy procedure using a trapezoidal-shaped wedge to elevate the lateral wall of the trochlea can be used with the goal of preventing further dislocation. However, outcomes studies are lacking, and scores on patient-reported outcome measures (PROMs) are largely unknown. Purpose/Hypothesis: The purpose of this study was to identify PROM scores for the Kujala Anterior Knee Pain Scale (AKPS), International Knee Documentation Committee (IKDC), Activity Rating System (ARS), and 100-point pain visual analog scale (VAS) for patients having undergone the modified Albee osteotomy. The hypothesis was that patients will have acceptable pain and function at mid- to long-term follow-up. Study Design: Case series; Level of evidence, 4. Methods: From 1999 to 2017, a total of 46 consecutive patients (49 knees) underwent a modified Albee procedure by a single surgeon at a single health care system. These 46 patients were contacted and asked to complete the AKPS, IKDC, ARS, and pain VAS. Additional demographic information was obtained via chart review. Frequencies and rates for categorical variables and means and standard deviations for continuous variables of the demographics and PROM scores were calculated. Results: PROM scores were obtained in 28 (30 knees; 61%) of the 46 patients. At minimum follow-up of 82 months, the mean scores were 78.5 ± 18.2 for AKPS, 61.2 ± 11.4 for IKDC, 5.2 ± 5.3 for ARS, and 24.4 ± 28.7 for VAS pain. Notably, only 1 of the 28 patients reported a patellofemoral dislocation since surgery, and this was an isolated incident without further instability. Conclusion: A modified Albee trochlear osteotomy can be a successful adjunctive procedure to prevent recurrent patellar dislocations in patients with mild TD. However, owing to the loss of one-third of patient follow-up scores and the absence of baseline function scores in this study, the procedure deserves further investigation as a way to address a particularly difficult dilemma for a select subset of patients with patellofemoral instability.